Gibalna dejavnost otrok z vidika socialnoekonomskih razsežnosti - Strniša, Klavdija; Planinšec, Jurij (Revija za elementarno izobraževanje, 2014)
Physical Activity for Children in Terms of Socio-Economic Dimensions. The purpose of this study was to analyse the physical activity of children in the first cycle of education in terms of socio-economic dimensions. The sample respondents included 132 children from four basic schools in north-eastern Slovenia. Data were collected through questionnaires and analysed with the statistical program SPSS. We used the t-test, ANOVA and post-hoc analysis to sum up the differences. The statistical significance of the results was assessed at the level of 5% of the risk. Results have shown that boys are more physically active than girls. The analysis showed that children from urban schools are physically active for twenty minutes a day more than children from rural schools. Education of children´s parents is statistically associated with the physical activity of children - the children of parents with the highest levels of education are physically the most active. Physical activity of a child´s father is statistically significant in relation to physical activity of his children. Despite the fact that especially in the last few years, the importance of physical activity for the development and health of children has been emphasised, there are still a lot of children who are insufficiently physically active. Many parents and children give the rapid tempo of life and the lack of time for a better quality of their life as excuses for this situation.